A qualitative study of cognitive, behavioral, and environmental influences on Hispanic mothers' early childhood feeding practices. (1st September 2021) - Lebron, Cynthia N.; Agosto, Yaray; Guzman, Tamisha; Sutton, Danielle; Stoutenberg, Mark; Messiah, Sarah E.; George, Sara M. St.
Abstract: Young children's lifestyle behaviors are largely shaped by their parents. There are socioeconomic risk factors particular to Hispanic populations that influence the way parents feed their children. As obesity continues to be a public health issue with substantial inequities across race and ethnicity, it is critical to understand Hispanic parents' food choices and feeding practices. The objective of this qualitative study is to identify the behavioral, environmental, and cognitive factors that influence the parental food choices and feeding behaviors of Hispanic mothers of children ages 0–5 years. Snowball sampling was used to recruit participants from the community (n = 30) who were 1) female; 2) Hispanic; 3) over the age of 18; and 4) a mother to child(ren) between the ages zero and five. Each interview consisted of a brief demographic survey and a set of open-ended questions based on Social Cognitive Theory constructs. A thematic analysis using a combined deductive and inductive approach was used to analyze transcriptions. Results indicated that mothers' attitudes around breastfeeding were connected with their challenges, while their attitudes around solid foods were expressed in their feeding strategies. Mothers used strategies of modeling, repeated exposure, and practices of "sneaking" in healthy foods and bribing to promote healthy eating. Mothers were most likely to seek out information from (1) pediatricians, (2) female family members, and (3) the internet. Hispanic mothers actively seek out information from many different sources that impact how they feed their young children. Understanding their trusted sources and how it influences the SCT constructs is an important step in preventing early childhood obesity.